Penal Mediation as an Alternative Dispute Resolution for Indonesian Criminal Code - Ratri Novita Erdianti; Wasis Suprayitno; Sholahuddin Al-Fatih (Universitas Slamet Riyadi, 2020)
A high level of criminality has caused several issues in upholding the criminal code. The issues include things that are related to the effective ways to tackle criminality, criminal cases accumulation, and over-capacity issue. These issues need a proper handle immediately. One of the resolution mechanisms of criminal cases is by using the restorative justice approach, namely penal mediation. This research is to analyze the penal mediation construction in Indonesia and its role as an attempt of criminal case policy as the update of Indonesian criminal law This research conducted a normative juridical analysis of a variety of legislation and crime prevention theories. Penal mediation is an alternative dispute resolution (ADR) outside the court which commonly applies to civil cases. Unlike the juvenile criminal justice system, the positive criminal law in Indonesia cannot resolve the criminal cases outside the court; nevertheless, certain cases make it possible to have it settled outside the court. Apart from that, as a discrete, Indonesian law enforcement also settles some criminal cases outside the court. For civil cases, the mediation usually in the case relate to finance issue, as for criminal case, it is more on freedom and life of an individual. Mediation for civil cases is usually directly among parties of the dispute, or the second party of interest. As for criminal cases, the parties are more complexs which include the actors, victims, but also the prosecutor and public.